Distal sleeve of false lumen occluder displacement through a proximal intimal re-entry potentially causing visceral malperfusion: A word of caution - Nabil Saouti, MD, PhD; Stijn Hazenberg, MD, PhD; Guillaume S.C. Geuzebroek, MD, PhD; Michel W.A. Verkroost, MD; Foeke J. Nauta, MD, PhD; Wilson L. Li, MD; Josst A. van Herwaarden, MD, PhD; Robin H. Heijmen, MD, PhD (Journal of Vascular Surgery Cases and Innovative Techniques, 2025)
We describe a patient treated with thoracic endovascular aortic repair and false lumen (FL) occluder for chronic type B aortic dissection. We noticed during open surgery for contained rupture that the distal unstented sleeve of the FL occluder crossed from the false into the true lumen through an intimal reentry (used for its introduction into the FL) potentially obstructing true lumen-originating renovisceral arteries.